2009
DOI: 10.1002/bjs.6783
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of a one-stop referral and management service for ruptured abdominal aortic aneurysms

Abstract: Patients with RAAA should be offered a one-stop emergency vascular service even if this involves further travel. Such a strategy offers significantly higher chance of intervention and survival from ruptured AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…Perioperative mortality is invariably higher (>40%) when nonintervention rates are reported. 15,16,19 In our series, the operative mortality was 51%. One may speculate that there is an inverse relationship between low nonintervention rates and high perioperative mortality.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Perioperative mortality is invariably higher (>40%) when nonintervention rates are reported. 15,16,19 In our series, the operative mortality was 51%. One may speculate that there is an inverse relationship between low nonintervention rates and high perioperative mortality.…”
Section: Discussionmentioning
confidence: 48%
“…Notably, most previous studies report a substantially higher nonintervention rate. 15,16 Lower nonintervention rates are rarely reported, with only two previous studies reporting numbers below 20% (19% and 9%, respectively), 18,19 and neither of these studies published the clinical or forensic autopsy rates in the relevant catchment areas. In our study, a substantial portion of the "nonintervention" patients were diagnosed post mortem (n ¼ 12) or were moribund or agonal (n ¼ 14) at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the patient is treated at the hospital were he primarily seeks medical care, even if this involves further travel, compared to a two---stop referral pattern, i.e. being transported from the hospital were the patient seeks primary care, to a hospital performing surgery for AAA (Hafez et al 2009). …”
Section: Changing Referral Patternsmentioning
confidence: 99%
“…For AAA ≥ 55 recent data suggested an annual risk of approximately 25% (Noronen et al 2013). According to a recent review (Reimerink et al 2013b), two studies reported the proportion of patients reaching surgery if rupture occurs (Acosta et al 2006, Hafez et al 2009). Synthesising data from these two studies yielded an estimated probability of reaching surgery of 39%.…”
Section: Prevalence Growth and Risk Of Rupturementioning
confidence: 99%